On the value sharing of $q$-$c$-shift and $q$-shift monomials of meromorphic functions and their derivatives - Banerjee, Abhijit; Biswas, Tania (Sarajevo Journal of Mathematics, 2024)
In this paper, we employ the notion of weighted sharing to study the uniqueness problems of $q$-$c$-shift and $q$-shift monomials of transcendental meromorphic functions of zero order sharing $1$-points. The results in this paper extend some previous results.